Oxford think new syallabus mathematics workbook 2 . - Ban Har, Yeap. (Karachi : Oxford university press, 2024)
Think !!!New Syllabus Mathematics is a series designed to foster both a deep understanding and appreciation of mathematics .Book typically focuses on equations and functions.
Keywords: Oxford mathematics workbook 2; Oxford-Mathematics workbook 2.